PENGARUH HARGA, PROMOSI, DAN PELAYANAN TERHADAP KEPUASAN PELANGGAN MAYBELLINE DI MATAHARI MALL CIPUTRA CIBUBUR - Agustini; Nurul Istikomah (Jurnal Gici Jurnal Keuangan dan Bisnis, 2021)
Competition in today's business world is getting tighter, causing more and more choices of cosmetic products sold by other large companies, such as those experienced by companies in Indonesia, The purpose of this study is to determine and analyze the effect of Price, Promotion and Service on Maybelline customer satisfaction at Matahari Mall Ciputra Cibubur. The research method used is a research method in the form of data collection using questionnaires. The data analysis model used is multiple linear regrenance analysis. Sample selection is done by purposive sampling. The sample amounted to 61 respondents, using multiple linear regrenances. The results of the regrenance test showed that 51.9% of customer satisfaction factors could be explained by price, promotion and service while the remaining 48.1% was influenced by other variables that were not included in this study. While the results of the F test show that simultaneously prices, promotions and services have a positive and significant effect on customer satisfaction with the results of the analysis, namely the value of Fcalculate (22.560) > from Ftable (2.77). The results of the t test show that the promotion variable shows.